Quality of MIS vs Open Joint Preparations of the Foot and Ankle. Issue 4 (November 2022) - Zhao, John Z.; Kaiser, Philip; Farina, Evan; DeGruccio, Christina M.; Miller, Christopher P.
Category: Other; Ankle; Hindfoot; Lesser Toes; Midfoot/Forefoot Introduction/Purpose: Minimally invasive surgery (MIS) is growing in the field of foot and ankle surgery, and the MIS burr is an emerging tool. While commonly used to perform osteotomies, the burr can also be utilized for arthrodesis joint preparation that traditionally would be performed through open incisions. To date, there is no study comparing the quality of joint preparation between using a fluoroscopy-guided MIS technique compared to traditional open techniques. The goal of this cadaveric study is to compare the percentage of joint surfaces prepared between MIS and open techniques, for the most common joints that are fused in foot and ankle surgery. Methods: Open joint preparation was performed under direct visualization with open incisions. MIS joint preparation was performed percutaneously using fluoroscopic guidance alone, without arthroscopy. After joint preparation, cadaveric samples were disarticulated, and joint surfaces were analyzed for percentage of cartilaginous surface removed. The percentage of joint surface prepared was compared between the open and MIS techniques. Results: Ten cadaveric samples were used for the MIS technique, and five samples for the open technique. Percentage of joint surface prepared was not statistically different for 15/17 joint surfaces. The MIS technique demonstrated statistically significant (p=0.048) better preparation than open in the talar head and the cuboid at the CC joint. Qualitative inspection of these two joints suggested the open technique frequently missed the most plantar surface of the talar head and the medial side of the CC joint, whereas the MIS technique performed better in these areas. Conclusion: The MIS technique provides similar percentages of surface area prepared compared to traditional open techniques. In certain joints with greater depth, the MIS technique may provide better joint preparation. This study suggests that MIS joint preparation is a reasonable, and possibly advantageous, alternative to open preparation in arthrodesis surgery when performed by experienced MIS surgeons.